The multi-detector computed tomographical analysis of bone density in impacted maxillary canines - Nidhal H Ghaib; Nadia B Al-Ansari (College of Dentistry/ University of Baghdad, 2014)
Background: Maxillary canines are important aesthetically and functionally, but impacted canines are more difficult and time consuming to treat, the aim of this study is to investigate with multi-detector computed tomography the correlation between the bone density and the upper canine impaction. Material and method: A sample of Unilaterally impacted maxillary canines from 24 patients (19 female, 5 male) who were referred to accurately localize the impacted canines at al- Karkh general hospital were evaluated by a volumetric 3-d images by the multi-detector computed tomography to accurately measure the bone density of the maxillary cortical palate of the maxillary impacted canine side and compare it with the other side of the normally erupted canine. Results: The statistical descriptive analysis showed that the ratio of the maxillary canine impaction was higher in females than in males, also the it revealed that the mean bone density of the cortical bone was greater in the maxillary impacted canine side (affected side) than in the control side (the side of the normally erupted canine), the Wilcoxon signed ranks test showed a significant difference in the mean bone density between the affected side and the control side. Conclusions: The increased bone density of the maxillary cortical plate could be an obstructive factor that cause maxillary canine impaction.